Reconstructing Administrative Remedies from the Perspective of Administrative Justice Principles and Legal Certainty - Wahyu Desiana; Zamroni Abdussamad; Erman Rahim (Journal of Public Representative and Society Provision, 2026)
This study examines the legal uncertainty arising from the disharmony between Law No. 5 of 1986 on Administrative Courts, Law No. 30 of 2014 on Government Administration, and PERMA No. 6 of 2018 on Guidelines for the Settlement of Government Administrative Disputes. The overlapping norms in these three regulations have caused confusion regarding the mandatory nature of administrative efforts, the finality of decisions, and the procedural consequences for citizens' rights to sue. This study uses a normative legal method with a legislative, conceptual, and comparative approach. The analysis was conducted qualitatively using a legal hermeneutic model to find the compatibility between norms and government practices. The results show that the administrative appeal system in Indonesia does not yet guarantee procedural certainty and substantive justice because it lacks uniform national standards regarding objection mechanisms, deadlines, and the independence of reviewing officials. The system is reconstructed by combining the theories of Administrative Justice and the Legal Certainty Framework, which emphasize the principles of norm clarity, proportionality, and procedural accountability. The proposed design includes a digital one-stop portal, written justification requirements, independent oversight, and the establishment of nationwide implementing regulations. The results of this study provide a conceptual contribution to the reform of Indonesian administrative law while strengthening the rule of law through fair, efficient, and transparent administrative efforts.